(3ebGdI GdEScfOQ GdEaQhOjSi aj EKHGJ GdUhQ GdQhMGfjI GdJi dGgjhdi dgGs - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd GdEScfOQ (B: (3Ef cd eG QLY Edi PGJg agh QhMGfi s
(3BNQgG (B:s
(3hhVM gGgfG CTjGA gi UhQ abW djS ajgG TF ef Gdgjhdi GdHJg JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/10) s
Keywords: (3GdadSaI hGdefWbs